8th gender and development lecture - School of Arts Management & Humanities, Edna Manley College of the Visual and Performing Arts.
This programme was done for the 8th Gender and Development Lecture. It was held on Thursday, February 23, 2016, at the Vera Moody Concert Hall.
Keywords: Programme. -- Jamaica